The sum 1 ⋅ 2 ⋅ 3 3 + 2 ⋅ 3 ⋅ 4 5 + 3 ⋅ 4 ⋅ 5 7 + ⋯ + 4 0 ⋅ 4 1 ⋅ 4 2 8 1 can be expressed as b a where a and b are coprime positive integers. What is the value of a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
how did you know the general term of the expression ?
Log in to reply
The general term of the expression is simply the "pattern" that occurs in each term. So, in the denominator you see the multiplication of three consecutive numbers, which is ( n − 1 ) n ( n + 1 ) , and in the numerator you see the middle number, multiplied by 2, minus one, which is simply 2 n − 1 . Whenever you see this kind of series, just look for the pattern that appears, or in mathematical terms, the general term of the sequence. I hope this helped; if you have any more questions please ask.
Log in to reply
yes..i do have more question....this general was pointed out just by looking at the numbers..what if the numbers are not so easy and what if we cant find out general term just by seeing it........what is the technique...please reply fast..it's my test at the end of this week.
Log in to reply
@Max B – Can you give me an example of a sequence where it's not easy to find the general term? I can't think of one off the top of my head.
Hey.. Babes.. U r a genious
The expression is equivalent to n = 2 ∑ n = 4 1 ( n − 1 ) ( n ) ( n + 1 ) 2 n − 1 and by partial fraction decomposition we see that it is also equivalent to n = 2 ∑ n = 4 1 n − 1 2 1 + n 1 + n + 1 − 2 3 Expanding the first few terms we notice for three consecutive n ; k , k + 1 , and k + 2 ; we have ( k + 2 ) − 1 2 1 + k + 1 1 + k + 1 − 2 3 = 0 Thus, the series telescopes. After all cancellations are made, the remaining terms are 2 − 1 2 1 + 2 1 + 3 − 1 2 1 + 4 0 + 1 − 2 3 + 4 1 1 + 4 1 + 1 − 2 3 Which is equivalent to 2 1 + 4 3 − 8 2 1 − 8 4 3 = 2 8 7 3 4 5 Thus, the answer is 3 4 5 + 2 8 7 = 6 3 2
How did you know that it is equivalent to that ?
Log in to reply
Put it like n − 1 A + n B + n + 1 C = n + 1 2 n − 1
Try equating coefficients of n , n 2 and constant terms. Find A , B and C and you have it. :-D
NOTE:The above is a method of reduction called the method of "partial fractions".
r = 1 ∑ 4 0 r ( r + 1 ) ( r + 2 ) 2 r + 1
= r = 1 ∑ 4 0 r ( r + 1 ) ( r + 2 ) ( r + 1 ) ( r + 2 ) − r ( r + 1 ) − 1
= r = 1 ∑ 4 0 ( r 1 − r + 2 1 ) − r = 1 ∑ 4 0 r ( r + 1 ) ( r + 2 ) 1
= r = 1 ∑ 4 0 ( r 1 − r + 1 1 ) + r = 1 ∑ 4 0 ( r + 1 1 − r + 2 1 ) - 2 1 r = 1 ∑ 4 0 ( r ( r + 1 ) 1 − ( r + 1 ) ( r + 2 ) 1 )
= 1 − 4 1 1 + 2 1 − 4 2 1 − 4 1 + 2 1 4 1 1 4 2 = 2 8 7 3 4 5
⇒ a + b = 6 3 2
We decompose into partial fractions that then telescope, so i = 1 ∑ 4 0 i ( i + 1 ) ( i + 2 ) 2 i + 1 = i = 1 ∑ 4 0 ( i + 1 1 + 2 i 1 − 2 ( i + 2 ) 3 ) = 2 1 + 2 1 + 4 1 + 4 1 1 − 8 2 3 − 8 4 3 = 2 8 7 3 4 5 and hence a + b = 3 4 5 + 2 8 7 = 6 3 2
The partial fractions decomposition of the general term n ( n + 1 ) ( n + 2 ) 2 n + 1 has the form n ( n + 1 ) ( n + 2 ) 2 n + 1 = n A + n + 1 B + n + 2 C . Multiplying both sides by n ( n + 1 ) ( n + 2 ) gives us 2 n + 1 = A ( n + 1 ) ( n + 2 ) + B n ( n + 2 ) + C n ( n + 1 ) . Substituting n = 0 gives us A = 2 1 ; substituting n = − 1 gives us B = 1 ; and substituting n = − 2 gives us C = − 2 3 . Therefore n ( n + 1 ) ( n + 2 ) 2 n + 1 = 2 n 1 + n + 1 1 − 2 ( n + 2 ) 3 and our sum can be written as ( 2 1 + 2 1 − 6 3 ) + ( 4 1 + 3 1 − 8 3 ) + ( 6 1 + 4 1 − 1 0 3 ) + ⋯ + ( 2 ( 4 0 ) 1 + 4 1 1 − 2 ( 4 2 ) 3 ) . Note that 2 ( n + 2 ) 3 = n + 2 1 + 2 ( n + 2 ) 1 , so that the last term in each triple − 2 ( n + 2 ) 3 cancels with the middle term in the next triple n + 2 1 and the first term of the triple after that 2 ( n + 2 ) 1 . The terms that do not cancel are the first two terms in the first triple, the first term in the second triple, the last term in the next-to-last triple, and the last two terms in the last triple. Hence, our sum equals ( 2 1 + 2 1 ) + ( 4 1 ) + ( − 2 ( 4 1 ) 3 ) + ( 4 1 1 − 2 ( 4 2 ) 3 ) . In reduced form this is equal to the fraction 2 8 7 3 4 5 , and thus a + b = 3 4 5 + 2 8 7 = 6 3 2 .
why did you put n as 0 then -1 and then -2...why only them ???
It can be written as:
= ( 1/2-1/3+1/3-1/4.......1/41-1/42 ) + 1/2[1/2-1/(41x42)]
= 20/21 + 215/861
= 1035/861 = 345/287
Ans. = 345 + 287 = 632
Dear Aman, you must learn how to use LaTeX .
Log in to reply
It takes time ....
Log in to reply
Aman, if I'm not wrong, do you have 2 Brilliant accounts??
Log in to reply
@Satvik Golechha – One is my brother's account. he has made it on my name
Log in to reply
@Aman Gupta – How are you on Calculus level 4? Do you know Calculus??
Note que essa soma pode ser escrita como o seguinte somatório: £(2n+1/n(n+1)(n+2)) de n igual 1 até 40
Esse somatório pode ser separado em dois:
£(1/(n+1)(n+2)) + £(1/n(n+2))
£(1/(n+1) - 1/(n+2)) + 1/2 £(1/n - 1/(n+2))
Analisando o primeiro somatório temos:
(1/2 - 1/3) + (1/3 - 1/4) + (1/4 - 1/5) +...+ (1/41 - 1/42) = 1/2 - 1/42 = 10/21
Analisando o segundo somatório:
1/2 [(1 - 1/3) + (1/2 - 1/4) + (1/3 - 1/5) +...+ (1/40 - 1/42)] =
= 1/2 (1 + 1/2 - 1/41 - 1/42) = 625/41×3×7
Assim:
£(2n + 1/n(n+1)(n+2)) = 5×2/3×7 + 5^4/3×7×41 = 345/287
By partial fraction the nth term is
(2n - 1)/{(n-1)n(n+1)= 1/{2(n-1)} + 1/n - (3/2)/(n+1)
= Sum{ ( 1/2 )/(n-1) -(1/2)/n } + Sum{ 1/n - 1/(n+1) } , n = 1 to 41
Telescopic series,
= {1/2 + 1/4 - 1/82 - 1/84 } + {1/2 -1/42 }
=345/287 =a/b
a + b =632
We can simplify this problem by using Partial Factor Decomposition
\frac{3}{\( 1 \times \( 2 \times 3 )} ) = 2 1 + 2 1 - 2 1
\frac{5}{\( 2 \times \( 3 \times 4 )} ) = 4 1 + 3 1 - 8 3 ...
By continuing this process we can arrive to the result
2 1 + 4 1 + 6 1 + ... + 8 0 1 + 4 2 + 6 2 + 8 2 + ... + 4 1 2 - 6 3 - 8 3 - 1 0 3 - ... - 8 4 3
which can be simplified into
2 1 (1 + \frac{1}{2} \ + \( \frac{1}{3} \ + ... + \( \frac{1}{40} \+ 2( \( \frac{1}{2} \ + \( \frac{1}{3} \ + \( \frac{1}{4} \ \( \frac{1}{5} \ + ... + \( \frac{1}{41} \ ) - 3( \( \frac{1}{3} \ + \( \frac{1}{4} \ + \( \frac{1}{5} \ + ... + \( \frac{1}{42} ))
which is also equal to
2 1 ( 1 + 2 3 - 4 1 1 - 4 1 3 )
which is equal to 2 8 7 3 4 5
therefore a = 345 and b = 287, a + b = 632
Problem Loading...
Note Loading...
Set Loading...
The general term of this expression is ( n − 1 ) n ( n + 1 ) 2 n − 1 . We simplify this expression so as to get a telescoping series: ( n − 1 ) n ( n + 1 ) 2 n − 1 = = = ( n − 1 ) n ( n + 1 ) n + ( n − 1 ) n ( n + 1 ) n − 1 ( n − 1 ) ( n + 1 ) 1 + n ( n + 1 ) 1 2 n − 1 1 − n + 1 1 + n 1 − n + 1 1 . Now, we substitute in the specific terms into our general expression to get 2 1 1 − 3 1 + 2 1 − 4 1 + ⋯ + 4 0 1 − 4 2 1 + 2 1 − 3 1 + 3 1 − 4 1 + ⋯ + 4 1 1 − 4 2 1 . After canceling like terms, we are left with 2 1 + 2 1 − 4 1 1 − 4 2 1 + 2 1 − 4 2 1 = = = = 2 1 + 2 1 + 4 1 − 4 2 1 − 8 2 1 − 8 4 1 1 − 8 2 1 + 8 4 1 8 3 4 4 4 4 1 4 0 2 8 7 3 4 5 . Hence, our answer is 3 4 5 + 2 8 7 = 6 3 2 .